COVID-19 Vaccine Development: Insights, Prospects and Challenges - Patel, Jainish; Patel, Prittesh; Akinmuyiwa, Victor (Journal of Current Viruses and Treatment Methodologies, 2020)
This paper explores the trends, issues and challenges confronting the successful vaccine development for the novel Coronavirus disease (COVID-19). Right from the commencement of the COVID-19 pandemic, no drugs or vaccine has been developed nor approved for treating those down with COVID-19. This year, the scientific community and the vaccine industry have been asked to respond urgently to SARS-COVID-2 pandemic. Presently numerous vaccine development platforms are under process and DNA- and RNA-based platforms showing great potential followed by recombinant-subunit vaccines. Through explorative research, it was established that companies involved in COVID-19 vaccine development are facing big challenges in the scientific, economic and logistical perspectives. Amongst these challenges are distrust, misinformation, and about understanding the immune system interaction with the vaccine being developed, as well as with the pathogen itself. Adjudged as insurmountable may be too early a conclusion. The race is on and progresses are being made. Proper understanding of trends, metrics and dynamics revolving around COVID-19 vaccine development is crucial in expanding possibilities for positive results from ongoing vaccine research. In this review, we spotlight on the most recent developments in COVID-19 vaccine, including top 10 early candidates that may hit the market in next few months.
Keywords: Coronavirus; COVID-19; Clinical trial; Infection; Vaccine